Risk Factors for Urinary Incontinence in Taiwanese Women Aged 20-59 Years - Ching-Hung Hsieh; Maw-Sheng Lee; Meng-Chih Lee; Tsung-Cheng Kuo; Chun-Sen Hsu; Shao-Tung Chang (Elsevier, 2008)
Objective: To assess the risk factors for urinary incontinence among Taiwanese women. Materials and Methods: A sample of 4,549 women was selected using a multistage random sampling protoco The women selected were interviewed face-to-face by well-trained interviewers. The usual risk factors, which included marital status, age, body mass index, menstrual status, alcohol intake, drug allergy, diabetes mellitus, hypertensio and gynecologic events, were evaluated. The factors were assessed by frequency analysis and logistic regressio analysis using a significance level of less than 0.05. Results: A total of 3,537 women were successfully interviewed, producing a response rate of 77.8% (3,735/4,549' The prevalence of urinary incontinence increased significantly with marriage (21.7%; 95% confidence interva Cl, 20.2-23.2), alcohol intake (24.9%; 95% Cl, 1 9.3-30.5), drug allergy (24.5%; 95% Cl, 1 9.9-29.2), diabete mellitus (40.3%; 95% Cl, 29.3-51.2), hypertension (30.1%; 95% Cl, 23.8-36.4), body mass index (odds ratic 1.05 per unit increase; 95% Cl, 1.02-1.09) and a previous gynecologic operation (25.5%; 95% Cl, 1 9.9-31.2). Ag was also a risk factor for urinary incontinence (odds ratio, 1.04; 95% Cl, 1.03-1.05), but there was no relationshi between urinary incontinence and parity, route of delivery, smoking or menstrual status. Conclusion: There is a high prevalence of urinary incontinence among women who suffer from diabetes o hypertension, or who have undergone a gynecologic operation, in particular hysterectomy. From a public healt viewpoint, it is important to promote better health education in order to improve understanding of urinar incontinence and its risk factors and to increase the awareness of the availability of mainstream treatment; [Taiwan J Obstet Cynecol 2008;47(2):1 97-202]